Foundation, process and legal method: understanding the foundation for judicial decisions in the light of the theory of law (Research, Society and Development, 2020)
The way how the judicial decisions are based has become a subject of great academic relevance, due to the existence of numerous historical factors that have altered the classic perspective, by which the judge acted as simple discoverer of the juridical norm contained in the legislated texts. In the new conception, the interpretation of law is the result of the interpretative process developed by the interpreter and is confused with the application of law. The reasons of judicial decisions assume, therefore, the rational demonstration character of the application of the law, is the reason by wich can't be limited or perfectly understood under the strictly procedural view. On the contrary, the reasons of decisions is linked to the theory of law, in what is conventionally called the methodology of the science of law. Thus, the way a decision is based depends on the theory of the law employed and the methodology derived from it. Brazilian law has ignored for many decades the changes in law enforcement, insisting on treating the basis of judicial decisions under the simply procedural spectrum, a scenario that has been profoundly altered by the Civil Procedure Code of 2015, and the adoption of a methodological syncretism by art. 489, §1 and 2.